Powieść "Biały bez" Nikołaja Roszczyna jako wyraz tęsknoty za utraconą ojczyzną (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The paper discusses the functoning of emigration and Russian theme in the Nikolay Roščyn’s (1896-1956) novel Bely bez. Nikolay Roščyn – one of the younger generation writers Russian diaspora in Paris before World War II. Novel Bely bez has been analized in the context of exterritoriality, missing, memory and Russia theme – categorries, that had a strong influence on Roščyn’s life and works.